Molecular Microbiology Diagnostic Principles and Practice - Persing, David H;Ed. Tenover, Fred C;Ed (ASM Press, 2016)
Presents the latest molecular diagnostic techniques to support clinical care and basic and clinical research. The authors-all experienced researchers and diagnosticians-have conducted a comprehensive review and evaluation of this rapidly evolving field and written a book that offers a broad range of practical guidance and techniques. Encapsulates the current state of the science and points to new avenues for research that will broaden the application and usefulness of molecular diagnostics.